2019
DOI: 10.1002/jctb.5975
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability assessment of the manufacturing process of a biological active pharmaceutical ingredient

Abstract: BACKGROUND Although the biopharmaceutical market grows rapidly, the environmental impacts of biopharmaceutical manufacturing have been hardly evaluated. The aim of the study is to comprehensively assess the environmental sustainability of a biologically‐produced active pharmaceutical ingredient (API) manufacturing process. For this purpose, an exergy analysis and an (exergetic) life cycle assessment were performed using primary (foreground system) and modeled data (background system). Infliximab, a monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…These articles were heterogeneous. One article focused on conducting an environmental impact assessment of a specific monoclonal antibody using a life cycle assessment approach (antibodies included infliximab and ustekinumab) (86). In contrast, seven articles focused on assessing the manufacturing processes associated with monoclonal antibodies in general.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These articles were heterogeneous. One article focused on conducting an environmental impact assessment of a specific monoclonal antibody using a life cycle assessment approach (antibodies included infliximab and ustekinumab) (86). In contrast, seven articles focused on assessing the manufacturing processes associated with monoclonal antibodies in general.…”
Section: Resultsmentioning
confidence: 99%
“…While one study highlighted water use during the sterilisation of multi-use equipment as a key contributor to environmental impacts of monoclonal antibody manufacturing (92), another study showed how the alternative-single use technologies/equipment production-were associated with electricity consumption, freshwater use, emissions, human toxicity non-cancer effects, and photochemical ozone formation (87). Compounding this heterogeneity of approaches, Gamiz et al (2019) pointed to the uncertainties associated with conducting LCAs given current data gaps in the supply chain of these production processes (86).…”
Section: Resultsmentioning
confidence: 99%
“…La información para el cálculo de exergía para cultivos es un poco limitada, ya que requiere de cálculos avanzados en el área de la biología y análisis del comportamiento energético en el interior de la célula [173]. Además de esto el acceso a la información correspondiente a la composición de las plantas en cada etapa de su crecimiento es limitado o nula, por lo que se vuelve imprescindible realizar suposiciones en algunas de las etapas para el cálculo de la exergía química de las corrientes.…”
Section: Limitaciones Y Discusionesunclassified
“…Rentería Gamiz et al [131] en el año 2019, evalúan la sostenibilidad ambiental de un proceso de manufactura de ingredientes activos para la industria farmacéutica, mediante la aplicación de análisis exergéticos y LCA. Por otro lado, Un análisis de exergía es aplicado en conjunto al LCA sobre un proceso de producción de cemento para evaluar el costo real ecológico de una de las industrias más energéticamente intensivas y con altas emisiones de CO2 [132].…”
unclassified
“…In many studies, the energy demand and environmental impact of biologics manufacturing have been evaluated by life cycle assessment; water for injection (WFI) has consistently been identified as a key factor [47][48][49][50][51][52][53][54]. While they are mostly used for chromatographic steps, typical product-specific volumes of cleaning-in-place (CIP) and sterilizing-in-place (SIP) are in the range of 4-20 m 3 WFI /kg mAb [48,50,[55][56][57][58]. Idris et al showed that, for a large-scale 20 m 3 mAb process (titer 2 g/L), 1.9 m 3 WFI /kg mAb is used just for Protein A chromatography [50].…”
mentioning
confidence: 99%